2013
DOI: 10.1075/scl.53
|View full text |Cite
|
Sign up to set email alerts
|

Fluency in Native and Nonnative English Speech

Abstract: This book takes a new and holistic approach to fluency in English speech and differentiates between productive, perceptive, and nonverbal fluency. The in-depth corpus-based description of productive fluency points out major differences of how fluency is established in native and nonnative speech. It also reveals areas in which even highly advanced learners of English still deviate strongly from the native target norm and in which they have already approximated to it. Based on these findings, selected learners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 213 publications
(137 citation statements)
references
References 0 publications
6
125
0
6
Order By: Relevance
“…However, it needs to be noted that the correlation is not very strong, suggesting the relationship between speech rate in L1 and L2 is not very strong either. As it was already observed, the available research studies have shown that speech rate is among those temporal measures of fluency which consistently correlate positively across L1 and L2 data (see the discussion of De Jong, 2009, 2013and Derwing et al, 2009, which is confirmed by our research findings.…”
Section: L1supporting
confidence: 80%
See 4 more Smart Citations
“…However, it needs to be noted that the correlation is not very strong, suggesting the relationship between speech rate in L1 and L2 is not very strong either. As it was already observed, the available research studies have shown that speech rate is among those temporal measures of fluency which consistently correlate positively across L1 and L2 data (see the discussion of De Jong, 2009, 2013and Derwing et al, 2009, which is confirmed by our research findings.…”
Section: L1supporting
confidence: 80%
“…The author himself and his colleagues applied it in their 'Ealing project' series of studies investigating the effect of task-design on taskperformance (Foster, 2001;Foster & Skehan, 1996, 2013Skehan & Foster 1997, 2012. More recently, the speed/breakdown/repair fluency distinction inspired a number of accounts following the CAF (complexity, accuracy, fluency) paradigm (Housen, Kuiken, & Vedder, 2012).…”
Section: Defining Fluencymentioning
confidence: 99%
See 3 more Smart Citations